EFFECTIVENESS OF THE READING-WRITING PROGRAM IN IMPROVING EARLY CHILDHOOD LITERACY SKILLS IN PLAYGROUPS - Astary Poku (International Journal of Teaching and Learning, 2024)
This research focuses on the effectiveness of a reading and writing program in improving literacy skills in early childhood in play groups. Literacy is an important basic skill in children's cognitive and academic development. Therefore, a well-designed reading and writing program can be a powerful tool in facilitating early childhood literacy development. Through literature studies, this research collects and analyzes various data sources, including academic journals, articles and relevant books to identify various approaches and methodologies in teaching reading and writing for early childhood and evaluate their effectiveness. The research results show that implementing a reading and writing program that involves rich interactions, interesting learning materials, and learning approaches that are appropriate to the child's developmental stage can significantly improve children's literacy skills. This program includes a variety of techniques, such as storytelling, word games, letter and sound recognition, and fun writing activities. The involvement of parents and caregivers in this process was also found to have a significant positive impact. However, challenges in implementing the program were also identified, including the need for adequate resources, comprehensive teacher training, and adaptation of the program to individual children's needs. The conclusion of this literature research shows that an effective reading and writing program requires collaboration between teachers, parents and children, as well as a strong understanding of the principles of effective literacy teaching based on the child's stage of development.